Developments of a multi-wavelength spectro-polarimeter on the Domeless Solar Telescope at Hida Observatory. (22nd May 2018) - Anan, Tetsu; Huang, Yu-Wei; Nakatani, Yoshikazu; Ichimoto, Kiyoshi; UeNo, Satoru; Kimura, Goichi; Ninomiya, Shota; Okada, Sanetaka; Kaneda, Naoki
Abstract: To obtain full Stokes spectra in multi-wavelength windows simultaneously, we developed a new spectro-polarimeter on the Domeless Solar Telescope at Hida Observatory. The new polarimeter consists of a 60 cm aperture vacuum telescope on an altazimuth mounting, an image rotator, a high-dispersion spectrograph, and a polarization modulator and an analyzer composed of a continuously rotating waveplate with a retardation that is nearly constant at around 127° in 500–1100 nm. There are also a polarizing beam splitter located close behind the focus of the telescope, fast and large format CMOS cameras, and an infrared camera. A slit spectrograph allows us to obtain spectra in as many wavelength windows as the number of cameras. We characterized the instrumental polarization of the entire system and established a polarization calibration procedure. The cross-talks among the Stokes Q, U, and V have been evaluated to be about 0.06%–1.2%, depending on the degree of the intrinsic polarizations. In a typical observing setup, a sensitivity of 0.03% can be achieved in 20–60 seconds for 500–1100 nm. The new polarimeter is expected to provide a powerful tool for diagnosing the 3D magnetic field and other vector physical quantities in the solar atmosphere.